2007
DOI: 10.1007/s12237-007-9001-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variability of Freshwater Plumes in a Semienclosed Estuarine–Bay System

Abstract: While the physical forcing mechanisms that govern the outflows of major rivers throughout the world are well documented in the literature, comparably less research has been done to examine the mechanisms that govern the contributions of small rivers and streams to coastal ocean systems. These rivers and streams provide a direct means for the transport of anthropogenic and terrigenous materials from watersheds to coastal oceans. This study describes the temporal and spatial variability of freshwater plumes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…The Ala Wai Canal watershed extends from the crest of the Ko'olau Range Ocean and Earth Science and Technology, Honolulu, HI, USA. out to a depth of ~ 30 m. Based on this atlas and our observations (Pawlak et al, 2009) (Giambelluca et al, 1986) (Macdonald et al, 1983;Wong, 1994;Tomlinson and De Carlo, 2003;Ostrander et al, 2008). During heavy storms, 24-hour rainfall can exceed 250 mm over coastal areas and 500 mm over the mountainous interior of the Ko'olau Range (Giambelluca et al, 1984).…”
Section: Description Of the Study Areamentioning
confidence: 64%
See 1 more Smart Citation
“…The Ala Wai Canal watershed extends from the crest of the Ko'olau Range Ocean and Earth Science and Technology, Honolulu, HI, USA. out to a depth of ~ 30 m. Based on this atlas and our observations (Pawlak et al, 2009) (Giambelluca et al, 1986) (Macdonald et al, 1983;Wong, 1994;Tomlinson and De Carlo, 2003;Ostrander et al, 2008). During heavy storms, 24-hour rainfall can exceed 250 mm over coastal areas and 500 mm over the mountainous interior of the Ko'olau Range (Giambelluca et al, 1984).…”
Section: Description Of the Study Areamentioning
confidence: 64%
“…During heavy storms, 24-hour rainfall can exceed 250 mm over coastal areas and 500 mm over the mountainous interior of the Ko'olau Range (Giambelluca et al, 1984). Runoff from these storms has pronounced effects on the physics, chemistry, and biology of Kāne'ohe Bay on the windward side of the island (De Carlo et al, 2007;Ostrander et al, 2008;Hoover and Mackenzie, 2009;Drupp et al, 2011). The effects of runoff in Māmala Bay on the south shore of O'ahu appear to be less dramatic (Laws et al, 1999), in part because of the lower rainfall and greater flushing.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Our results are relevant depending on the range of the water level fluctuation and the frequency of data capture. For instance, Kröger et al (2008) and Ostrander et al (2008), with the same logger model that we used, measured streamflows and tide amplitudes, and placing the external logger at 1.5 or 4 m above ground, respectively. Both the purpose of those research studies and the temporal scale of measured water fluctuations did not show any of the possible instrumental and methodological uncertainties.…”
Section: Discussionmentioning
confidence: 99%
“…Dissolved nutrients are likely to be taken up most efficiently under baseflow conditions when freshwater inputs occur at low but steady rates. Although storms result in large inputs of dissolved nutrients to coastal waters, inputs occur as large pulses and storm conditions frequently are unfavorable for nutrient uptake [e.g., low light due to cloud cover and elevated turbidity, rapid mixing of plumes into lownutrient coastal waters by wind and waves (Ostrander et al 2008) resulting in dilution of nutrients], so changes in storm fluxes of dissolved nutrients may not impact coastal ecosystems as much as changes in baseflow fluxes. When storm plumes persist for extended periods, elevated nitrogen concentrations can support phytoplankton and zooplankton blooms (Ringuet and Mackenzie 2005;Hoover et al 2006), and the increased SRP concentrations found in urban runoff might extend bloom durations for longer periods than would otherwise be observed (e.g., Ringuet and Mackenzie 2005).…”
Section: Discussionmentioning
confidence: 99%